The lives of LGBT older adults : understanding challenges and resilience - Orel, Nancy A.; Fruhauf, Christine A. (American Psychological Association, 2015)
"Researchers and practitioners have become increasingly aware that LGBT persons have unique and varying needs. However, there is a dearth of empirical research on the specific needs and concerns of LGBT older adults and their families because sexual orientation as a research variable is basically absent in all major gerontological research studies. As a result, it is apparent that the available research on the specific needs and concerns of this "invisible" minority group must be made visible and accessible to all professionals who work with the older adult population. Thus, this book represents a comprehensive overview of cutting-edge research on LGBT older adults and their families. The primary purpose of the book is to inform researchers, practitioners, and policymakers of key research findings and describe practical implications for policy and practice related to LGBT aging individuals and families. Another key aspect of this book is its focus on the strengths and resiliency of the LGBT older adult population and the innovative ways in which individuals have overcome heterosexism and homophobia throughout their lives. The focus on strengths and resiliency is an important advancement in the field given that much of the previous literature on LGBT older adults neglected to address such topics"--Introduction. (PsycINFO Database Record (c) 2014 APA, all rights reserved)